How Will the Patient Protection and Affordable Care Act Affect Liability Insurance Costs? - David I. Auerbach, Paul Heaton (RAND Corporation, 2014)
private coverage and Medicaid while making major changes to payment rates and the health care delivery system in a number of areas. Although considerable analysis has been devoted to understanding the impacts of reform on health care providers, insurers, and patients, less attention has been given to other payers that fund health care services, such as property and casualty insurers and workers’ compensation (WC) programs. This report identifies a number of potential mechanisms through which the ACA might affect claim costs for liability insurers.1 For each mechanism, we discuss the conceptual basis for the mechanism, review existing scholarly evidence regarding the importance of the mechanism, and, where possible, attempt to use reasonable assumptions based on existing data to develop rough estimates of the size and direction of expected impacts as of 2016, when the ACA is expected to be fully in force. We discuss how each mechanism might operate across different liability lines and provide examples of how variation across states in existing legal rules, population demographics, and other relevant factors might mediate the operation of each mechanism. There is considerable uncertainty in our estimates, which are intended as broad indicators of sign and magnitude but are reported here quantitatively for convenience and to facilitate comparison between states and impacts. There are also other effects that could be large (such as systemic effects of ACA-induced changes to health care delivery) but that are extremely difficult to pinpoint. Some of these are discussed in Chapter Five of this report.